Efeitos da auditoria fiscal sobre a arrecadação do ICMS do Estado do Ceará - Arruda, José Alberto de Sabóia (2015)
In recent years, some studies related to the economy of tax evasion in Ceará have been conducted in order to verify evasive behavior in relation to the calculation and payment of VAT in post monitoring periods. This paper, as a contribution to the discussion and research in this area, the objective study of the impact on spontaneous ICMS collection, in 2013 compared to the year 2011, taxpayers were audited, compared to those who do not underwent this procedure. In order to verify the impacts of the tax audit policy, you use the Linear Regression Model by OLS - OLS to differences in differences estimator, in which the treatment group consisted of 465 taxpayers was checked year 2012 and the control group consisted of 1,407 taxpayers who were not monitored during this period. Complemented the study using the quantile regression model aimed at analyzing the effect of the tax audit activity in ICMS collection by quantiles of the sample. The results of the empirical analysis showed that the tax audit in 2012 had no effect on the collection of VAT in 2013 compared to 2011. It was observed that the Tax Administration has prioritized tax audit taxpayers that have a large potential revenue collection and are not influenced in their behavior in the period immediately following the submission of tax audit.